FITOREMEDIASI LIMBAH YANG MENGANDUNG TIMBAL (Pb) DAN KROMIUM (Cr) DENGAN MENGGUNAKAN KANGKUNG AIR (Ipomoea aquatica) - Imbar Agusetyadevy; Sri Sumiyati; Endro Sutrisno (Jurnal Teknik Lingkungan, 2013)
AbstractHeavy metal contamination of waste containing lead (Pb) and chromium (Cr) is a serious problem on the current environmental conditions. Many industries that lead to increased pollution of water sources from waste discharged into waters without first processing. One of the processing environment is contaminated with lead and chromium phytoremediation technology. Plants absorb Pb and Cr potentially one of the plant water spinach (Ipomoea aquatica). The study was conducted to determine how much decrease in the concentration of lead (Pb) and chromium (Cr) and for analysis of wet plant water spinach (Ipomoea aquatica) and the long residence time of optimum to reduce waste containing concentrations of lead (Pb) and chromium (Cr) . Results of the study was a large decrease in Pb concentration of 0.5 mg/l and 0.8 mg/l by the swamp water, reaching 0.001 mg/l and 0.034 mg/l. While the decline in the concentration of Cr 1.5 mg/l and 2 mg/l was 0.25 mg/l and 0.623 mg/l. Analysis of wet kale optimum water is 100 grams. The method of absorption of Pb and Cr concentrations by water spinach is rhizofiltrasi and fitoekstraksi.